1988
DOI: 10.1016/0735-1097(88)91535-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety and diagnostic accuracy of dipyridamole-thallium imaging in the elderly

Abstract: The noninvasive diagnosis of coronary artery disease in the elderly can occasionally be difficult. Intravenous dipyridamole-thallium imaging is a potentially useful diagnostic test to determine presence and severity of coronary disease; however, the safety of the procedure has not been determined in an older population. The side effect profile and frequency of severe ischemic responses after 0.56 mg/kg of intravenous dipyridamole were compared in 101 patients greater than or equal to 70 years old and 236 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The topical application of adenosine receptor agonists or agents that increase endogenous adenosine levels has the advantage that the effects of the agents are concentrated locally and that fewer systemic toxicities develop because little of the agent is released systemically. Moreover, dipyridamole has been used systemically (both orally and intravascularly in patients) for decades with little systemic toxicity; the occurrence of severe drug-related adverse effects, including cardiac death, sustained ventricular arrhythmia, cerebral ischemic attack, stroke, or severe bronchospasm, is ,0.02% of patients taking systemic doses of the agent (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…The topical application of adenosine receptor agonists or agents that increase endogenous adenosine levels has the advantage that the effects of the agents are concentrated locally and that fewer systemic toxicities develop because little of the agent is released systemically. Moreover, dipyridamole has been used systemically (both orally and intravascularly in patients) for decades with little systemic toxicity; the occurrence of severe drug-related adverse effects, including cardiac death, sustained ventricular arrhythmia, cerebral ischemic attack, stroke, or severe bronchospasm, is ,0.02% of patients taking systemic doses of the agent (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…After the collection of clinical data for submission to regulatory authorities in the United States, additional studies were published that demonstrate the diagnostic usefulness of dipyridamole-thallium scintigraphy. 8,9 This study focuses on the safety of dipyridamole-thallium scintigraphy with an analysis of the clinical safety data that were collected from investigators in the United States who had performed thallium myocardial imaging using intravenous dipyridamole.…”
Section: Intravenous Dipyridamole Thallium Imaging Study Groupmentioning
confidence: 99%
“…It is more than likely that some of these patients had coexisting carotidartery disease. Finally, the safety of intravenous dipyri damole TMI has also been assessed in coronary patients older than 70 years in whom carotid-artery disease is even more probable [32], In previous studies, dipyridamole TMI was employed for the detection of IHD in patients with peripheral or abdominal aortic vascular disease [33][34][35][36][37], In all studies, it was found to have prognostic utility for risk stratifica tion before vascular surgery. The risk of perioperative events, i.c.…”
Section: Discussionmentioning
confidence: 99%